On the association of lunar daily variations in H at Alibag with the degree of magnetic activity - Rao, D.R.K.; Arora, B.R. (My University, 1975)
The lunar semidiurnal term of the phase law tides in the horizontal intensity at Alibag is found to undergo a systematic decrease in amplitude with increase in magnetic activity. An examination of the results reported earlier for some stations and those of Alibag suggests that there is a general decrease of amplitude with increase in magnetic activity at stations where the lunar time of maximum is around the time of magnetospheric expansion for the lunar tide and an increase in amplitude for stations where the lunar time of maximum is around the time of magnetospheric contraction. In the partial tides, only the phase angle of the second harmonic shows a systematic decrease with increase in magnetic activity.
Keywords: Diurnal variations; Flux density; Geomagnetism; Lunar tides; Magnetic variations; Magnetospheric Instability; Harmonic functions; Lunar effects; olar activity effects; Solar wind velocity